First record of the invasive snail Melanoides tuberculatus (Gastropoda: Prosobranchia: Thiaridae) in the Paranã River basin, GO, Brazil - Rocha-Miranda, F. (2006)
The Thiarid snail Melanoides tuberculatus (Müller, 1774), native to Asia and East Africa was recorded for the first time in the Paranã River basin, Goiás State. There is no evidence concerning introduction vectors but aquarium releases is the most probable vector. Specimens were collected at three different water bodies after twenty-seven rivers were investigated. The possible spread of this species to other habitats and potential effects on native thermal water communities are discussed.